Change Pattern of Land Use of Jabodetabek Area Through Irio and Dimamic System Approach - Yunus Arifien; Ernan Rustiadi (Agricultural Science, 2019)
The objectives of this research are to examine: (11) patterns of land use change in Jabodetabek and (2) the inter-sector and inter-spatial linkage models in changes in agricultural land use.. The research was conducted by using the analysis of Geographic Information System (GIS), Inter Regional Input-Output (IRIO) and dynamic systems. The result shows that land use change from agricultural land into built up area during 1972-2017 where the built-up area in Jakarta becomes wider with the periphery becomes larger by following of the area where the transportation infrastructure has been built well through rail road or toll road, artery road and Jakarta outer ring road. The change of land use is also influenced by economic linksages among Jakarta Province, Bogor-Depok-Tangerang-Bekasi (Bodetabek) region, and outer of Jabodetabek region. In general, scenario model 2 is the best choice, which provides an impact on the best land use change and the increase impact of economic growth.